Seizure-induced overexpression of NPY induces epileptic tolerance in a mouse model of spontaneous recurrent seizures - Drexel, Meinrad; Sperk, Günther (Frontiers in Molecular Neuroscience, 2022)
Epileptic seizures result in pronounced over-expression of neuropeptide Y (NPY). In vivo and in vitro studies revealed that NPY exerts potent anticonvulsive actions through presynaptic Y2 receptors by suppressing glutamate release from principal neurons. We now investigated whether seizure-induced over-expression of NPY contributes to epileptic tolerance induced by preceding seizures. We used a previously established animal model based on selective inhibition of GABA release from parvalbumin (PV)-containing interneurons in the subiculum in mice. The animals present spontaneous recurrent seizures (SRS) and clusters of interictal spikes (IS). The frequency of SRS declined after five to six weeks, indicating development of seizure tolerance. In interneurons of the subiculum and sector CA1, SRS induced over-expression of NPY that persisted there for a prolonged time despite of a later decrease in SRS frequency. In contrast to NPY, somatostatin was not overexpressed in the respective axon terminals. Contrary to interneurons, NPY was only transiently expressed in mossy fibers. To demonstrate a protective function of endogenous, over-expressed NPY, we injected the selective NPY-Y2 receptor antagonist JNJ 5207787 simultaneously challenging the mice by a low dose of pentylenetetrazol (PTZ, 30 or 40 mg/kg, i.p.). In control mice, neither PTZ nor PTZ plus JNJ 5207787 induced convulsions. In mice with silenced GABA/PV neurons, PTZ alone only modestly enhanced EEG activity. When we injected JNJ 5207787 together with PTZ (either dose) the number of seizures, however, became significantly increased. In addition, in the epileptic mice CB1 receptor immunoreactivity was reduced in terminal areas of basket cells pointing to reduced presynaptic inhibition of GABA release from these neurons. Our experiments demonstrate that SRS result in overexpression of NPY in hippocampal interneurons. NPY overexpression persists for several weeks and may be related to later decreasing SRS frequency. Injection of the Y2 receptor antagonist JNJ 5207787 prevents this protective action of NPY only when release of the peptide is triggered by injection of PTZ and induces pronounced convulsions. Thus, over-expressed NPY released “on demand” by seizures may help terminating acute seizures and may prevent from recurrent epileptic activity.